2016
DOI: 10.1016/j.ophtha.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Myopia and High Myopia and Temporal Trends from 2000 through 2050

Abstract: Myopia and high myopia estimates from 2000 to 2050 suggest significant increases in prevalences globally, with implications for planning services, including managing and preventing myopia-related ocular complications and vision loss among almost 1 billion people with high myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
2,445
8
69

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 3,262 publications
(2,814 citation statements)
references
References 22 publications
35
2,445
8
69
Order By: Relevance
“…As a consequence, the prevalence of high myopia is also on the rise. It is said that by 2050, nearly 10% of the global population will have high myopia with the prevalence being much higher in Asian countries 20. And indeed, prevalence of high myopia is already high in many parts of Asia9, 10, 11, 21, 22 and is one of the leading causes of vision impairment and blindness in adults 23, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the prevalence of high myopia is also on the rise. It is said that by 2050, nearly 10% of the global population will have high myopia with the prevalence being much higher in Asian countries 20. And indeed, prevalence of high myopia is already high in many parts of Asia9, 10, 11, 21, 22 and is one of the leading causes of vision impairment and blindness in adults 23, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…Myopic and especially highly myopic eyes are more susceptible to pathological ocular changes including cataract, glaucoma, retinal detachments and myopic macular degeneration, all of which can lead to legal blindness. HM is the fourth most common cause of irreversible vision loss and a public health problem imposing an enormous economic and social burden in many countries including western ones, China or Japan [7][8][9][10]. Despite active research the exact mechanisms that govern myopic eye growth are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed that myopia incidence is more among Asian countries with the prevalence of 70-90%. 3 According to WHO-NPCB survey in 1989, 1.49% population is blind of which 7.35% is due to refractive error. In the study conducted in 2001 prevalence of myopia at an urban population was 7.45% and 4.1% in rural population.…”
Section: Introductionmentioning
confidence: 99%